HEALTH WORKERS’ PERSPECTIVES ON DEVELOPING AN EFFECTIVE MODEL FOR SEXUAL AND REPRODUCTIVE HEALTH EDUCATION FOR ADOLESCENTS WITH INTELLECTUAL DISABILITIES: A QUALITATIVE STUDY IN PANGKALPINANG CITY - Putri Rhadiyah; Akhiat; Nita Arisanti; Hadi Susiarno; Meita Dhamayanti; Dewi Dhamayanti; Ruswana Anwar (Universitas Airlangga, 2025)
Introduction: Around 180 to 220 million young people are living with a disability and almost 80% are in developing countries. Adolescents with intellectual disabilities (ID) face heightened risks of inappropriate sexual behavior, sexual violence, and reproductive health issues due to limited access to tailored education. Health professionals have a responsibility to educate, inform, and support adolescents with intellectual disabilities regarding their sexual and reproductive health. Aims: The purpose of this study was to explore sexual and reproductive health education for adolescents with intellectual disabilities based on the perspective of health workers. Methods: A qualitative case study was conducted with 12 health workers from four primary health centers in Pangkalpinang City. Data were collected through in-depth interviews and analyzed using content analysis. Result: Analysis yielded 47 transcripts, 150 codes, 9 categories, and 4 overarching themes: Modelling, Guided Practice, Reinforcement, and Feedback. Under Modelling, key categories included the use of tangible learning media, focused educational content and adaptive communication techniques. Guided Practice involved live demonstrations, small-group settings, structured time management, and parental involvement. Reinforcement primarily took the form of positive feedback. Informants emphasized that effective sexual and reproductive health education must be repetitive, interactive, and involve parents as co-educators. Conclusion: Sexual and reproductive health education for adolescents with intellectual disabilities based on the perspective of health workers is formed by modelling, guided practice, reinforcement and feedback. These findings provide a practical, evidence-based framework for developing standardized sexual and reproductive health programs and training curricula for health workers in similar settings.